Comparison of Effectiveness of Pressure Support and Mandatory Ventilation Modes at the End of General Combined Anesthesia - V. A. Pyzhov; K. N. Khrapov; V. M. Miroshkina (Вестник анестезиологии и реаниматологии, 2022)
The objective: to compare effectiveness of pressure support and mandatory ventilation modes at the final stage of general anesthesia.Subjects and Methods. 58 patients were included in the study. All patients underwent laparoscopic or open surgery under combined general anesthesia with muscle relaxants and tracheal intubation. At the end of the operation, after suturing the muscle layer, patients were randomly divided into two groups, depending on the further mode of ventilation: the mandatory mode group with dual control until extubation (n = 29) and the spontaneous breathing mode group with pressure support (n = 29). The time of awakening, the severity of post-extubation cough, hemodynamic parameters and oxygenation immediately before and 5 minutes after extubation were assessed.Results. In the groups of patients, statistically significant differences were observed in the time of awakening (252 ± 67 sec and 426 ± 71 sec in PSV and PCV-VG Groups, respectively), extubation (287 ± 55 sec and 464 ± 67 sec in the PSV and PCV-VG groups, respectively), and transfer from the operating room (473 ± 60 sec and 687 ± 77 sec in the PSV and PCV-VG groups, respectively) (p < 0.0001). Also, patients receiving PSV respiratory support had higher saturation levels 5 minutes after extubation (p < 0.0001), and heart rate and mean arterial pressure immediately before extubation were lower than in the mandatory ventilation group (p = 0.013 and p < 0.0001, respectively). In addition, in the mode of spontaneous breathing with pressure support, a lower severity of post-extubation cough was observed (p = 0.003).Conclusion. The use of a spontaneous breathing mode with pressure support at the end of general combined anesthesia has several advantages versus mandatory ventilation mode. These advantages include faster awakening, extubation and transfer of the patient to the ward, lower severity of post-extubation cough, as well as better gas exchange after extubation, lower intensity of hypertension and tachycardia before it.